2001
DOI: 10.2527/2001.7941059x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of titanium dioxide as a digestibility marker for cattle.

Abstract: Three studies were conducted to evaluate titanium dioxide (TiO2) as a digestibility marker for cattle. In Exp. 1, eight steers consumed prairie hay ad libitum with or without dietary supplements. Fecal recovery of TiO2 averaged 93% and was not affected (P = 0.47) by supplement. Digestibilities calculated with reference to TiO2 were not different (P = 0.15) from those based on total fecal collections. In Exp. 2, two steers were limit-fed corn-based diets. Fecal recovery of TiO2 averaged 95% and that of chromic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
147
2
21

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(176 citation statements)
references
References 6 publications
6
147
2
21
Order By: Relevance
“…ME and digestible organic matter (DOM) concentrations were estimated by the Hohenheim Gas Test according to Close and Menke (1986). Total fecal excretion was calculated from the administered amount of TiO 2 , the TiO 2 concentration in fecal OM (Lippke, 2002) and the recovery rate of TiO 2 for ruminants of 0.93 (Titgemeyer et al, 2001). The CP (5N 3 6.25) concentration in fecal OM was used to estimate diet OM digestibility (Lukas et al, 2005).…”
Section: Experimental Designmentioning
confidence: 99%
“…ME and digestible organic matter (DOM) concentrations were estimated by the Hohenheim Gas Test according to Close and Menke (1986). Total fecal excretion was calculated from the administered amount of TiO 2 , the TiO 2 concentration in fecal OM (Lippke, 2002) and the recovery rate of TiO 2 for ruminants of 0.93 (Titgemeyer et al, 2001). The CP (5N 3 6.25) concentration in fecal OM was used to estimate diet OM digestibility (Lukas et al, 2005).…”
Section: Experimental Designmentioning
confidence: 99%
“…Inert markers must maintain digestive transit at the same speed as other dietary nutrients in the tract and be physiologically inactive, as well as being non-toxic, easily analysed, able to be homogenously mixed into a diet, indigestible and non-absorbed (Jagger et al, 1992;Titgemeyer et al, 2001). Titanium dioxide (TiO 2 ) has some advantages over the commonly used chromic oxide (Cr 2 O 3 ), with studies showing improvements in reproducibility and homogeneity (Jagger et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) has some advantages over the commonly used chromic oxide (Cr 2 O 3 ), with studies showing improvements in reproducibility and homogeneity (Jagger et al, 1992). TiO 2 is also approved for use as a feed additive by the Food and Drug Administration, unlike Cr 2 O 3 (Titgemeyer et al, 2001). Another commonly used marker is acid-insoluble ash, but it has been suggested that its digestive transit does not accurately reflect that of feed passage (Cheng and Coon, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marker methods overcome some difficulties that are encountered with the analysis of the ingesta/egesta method: stressful conditions for the animals (depending on the kind of harness and/or the width of stalls) and longer experimental periods. In recent years, indigestible markers have been used in digestibility trials: some markers are naturally occurring substances such as n-alkanes , acid-insoluble ash (AIA) (Miraglia et al, 1999a and1999b;Almeida et al, 2001) and acid detergent lignin (ADL) (Miraglia et al, 1999a and1999b), while other markers are added to diets, such as chromic oxide (Cr 2 O 3 ) in horses (Parkins et al, 1982;Cuddeford and Hughes, 1990) or titanium dioxide (TiO 2 ) in cattle (Titgemeyer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%